The Family Of The Qozilars: A Study Of Ustuvoi Scientific Legacy - Bahromov Sunnatilla Hamidjon ugli (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
Many scholars and intellectuals from the regions of Mavarannahr and Khorasan have significantly contributed to broadening worldviews and shaping intellectual abilities. This article is dedicated to the scientific legacy and life of Sayyid ibn Muhammad Ustuvoi, a distinguished scholar born in the village of Ustuvo in Khorasan, who holds a special place among Eastern intellectuals. Information about his pursuit of knowledge, teaching activities, and his contributions to his village can be found in numerous historical works. Studying his life is essential for advancing research aimed at renewing the educational and spiritual heritage of the East.